Reduction of Drosophila Mitochondrial RNase P in Skeletal and Heart Muscle Causes Muscle Degeneration, Cardiomyopathy, and Heart Arrhythmia - Saoji, Maithili; Petersen, Courtney E.; Sen, Aditya; Tripoli, Benjamin A.; Smyth, Jeremy T.; Cox, Rachel T. (Frontiers in Cell and Developmental Biology, 2022)
In this study, we examine the cause and progression of mitochondrial diseases linked to the loss of mtRNase P, a three-protein complex responsible for processing and cleaving mitochondrial transfer RNAs (tRNA) from their nascent transcripts. When mtRNase P function is missing, mature mitochondrial tRNA levels are decreased, resulting in mitochondrial dysfunction. mtRNase P is composed of Mitochondrial RNase P Protein (MRPP) 1, 2, and 3. MRPP1 and 2 have their own enzymatic activity separate from MRPP3, which is the endonuclease responsible for cleaving tRNA. Human mutations in all subunits cause mitochondrial disease. The loss of mitochondrial function can cause devastating, often multi-systemic failures. When mitochondria do not provide enough energy and metabolites, the result can be skeletal muscle weakness, cardiomyopathy, and heart arrhythmias. These symptoms are complex and often difficult to interpret, making disease models useful for diagnosing disease onset and progression. Previously, we identified Drosophila orthologs of each mtRNase P subunit (Roswell/MRPP1, Scully/MRPP2, Mulder/MRPP3) and found that loss of each causes lethality and decreased mitochondrial tRNA processing in vivo. Here, we use Drosophila to model mtRNase P mitochondrial diseases by reducing the level of each subunit in skeletal and heart muscle using tissue-specific RNAi knockdown. We find that mtRNase P reduction in skeletal muscle decreases adult eclosion and causes reduced muscle mass and function. Adult flies exhibit significant age-progressive locomotor defects. Cardiac-specific mtRNase P knockdowns reduces fly lifespan for Roswell and Scully, but not Mulder. Using intravital imaging, we find that adult hearts have impaired contractility and exhibit substantial arrhythmia. This occurs for roswell and mulder knockdowns, but with little effect for scully. The phenotypes shown here are similar to those exhibited by patients with mitochondrial disease, including disease caused by mutations in MRPP1 and 2. These findings also suggest that skeletal and cardiac deficiencies induced by mtRNase P loss are differentially affected by the three subunits. These differences could have implications for disease progression in skeletal and heart muscle and shed light on how the enzyme complex functions in different tissues.